2015
DOI: 10.1111/bph.13375
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol sensitizes breast cancer cells to TNF‐α induction of apoptosis by inhibiting Nur77 expression

Abstract: BACKGROUND AND PURPOSEThe orphan nuclear receptor Nur77 is implicated in the survival and apoptosis of cancer cells. The purpose of this study was to determine whether and how Nur77 serves to mediate the effect of the inflammatory cytokine TNF-α in cancer cells and to identify and characterize new agents targeting Nur77 for cancer therapy. EXPERIMENTAL APPROACHThe effects of TNF-α on the expression and function of Nur77 were studied using in vitro and in vivo models. Nur77 expression was evaluated in tumour ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
(109 reference statements)
0
21
0
Order By: Relevance
“…13,[23][24][25][26][27][28] Intravenous administration of chemotherapeutic agents has been accepted as a conventional approach for antitumor chemotherapy. However, the hydrophobicity of PTX and HK had limited its use in clinical practice.…”
mentioning
confidence: 99%
“…13,[23][24][25][26][27][28] Intravenous administration of chemotherapeutic agents has been accepted as a conventional approach for antitumor chemotherapy. However, the hydrophobicity of PTX and HK had limited its use in clinical practice.…”
mentioning
confidence: 99%
“…Figure 6). 19 In our study, we found that NR4A1 was highly expressed in TRAIL-resistant HCC cells. ISG12a-S has a stronger ability to induce apoptosis than the full length ISG12a.…”
Section: Trail Induces Nr4a1 Expression Partly Through Nf-κb Pathwaymentioning
confidence: 52%
“…19 The siRNA sequences To obtain a high knockdown efficiency, 50 nmol/L siRNA was used. 19 The siRNA sequences To obtain a high knockdown efficiency, 50 nmol/L siRNA was used.…”
Section: Plasmids and Sirna Transfectionmentioning
confidence: 99%
See 2 more Smart Citations